2021
DOI: 10.46328/ijres.2328
|View full text |Cite
|
Sign up to set email alerts
|

Employment, Employability, and Competencies of the Bachelor of Secondary Education Graduates

Abstract: Tracing graduates has become an imperative for higher education institutions much more during the pandemic. This tracer determined the employment and employability status of the 2019 BSE graduates and identified the competencies they adequately acquired and deemed vital for work. It used descriptive design, and data were collected from the 103 graduates through a Google form with open and closed-ended questions administered between November and December 2020. Results revealed that most of the graduates had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…To add, these competencies were adequately acquired by most of the 2019 graduates at Bukidnon State University. However, a few reported they acquired these skills inadequately (Caingcoy et al, 2021). This result is consistent with a claim that communication skills were on top among the surveyed skills (Negro et al, 2017).…”
Section: Communicationsupporting
confidence: 85%
See 4 more Smart Citations
“…To add, these competencies were adequately acquired by most of the 2019 graduates at Bukidnon State University. However, a few reported they acquired these skills inadequately (Caingcoy et al, 2021). This result is consistent with a claim that communication skills were on top among the surveyed skills (Negro et al, 2017).…”
Section: Communicationsupporting
confidence: 85%
“…Recently, our study revealed that the employability skills of Bachelor of Secondary Education graduates include communication, information and communication technology, pedagogy, time management, flexibility, leadership, and classroom management skills (Caingcoy et al, 2021). This was consistent in the study of Biscante et al (2019) wherein communication skills were deemed most useful in work.…”
supporting
confidence: 89%
See 3 more Smart Citations